Пошаговое объяснение:
(3а + 6в)/2 = 5
3а + 6в = 5 * 2
3а + 6в = 10
3а = 10 - 6в | : 3
а = 10/3 - 6/3в
а = 3 1/3 - 2в
-(4а + 2,1в) + (0,4в - 3,3а) - (1,7в - 5,9а) =
-4а - 2,1в + 0,4в - 3,3а - 1,7в + 5,9а =
(-4а - 3,3а + 5,9а) + (-2,1в + 0,4в - 1,7в) =
-1,4а + (-3,4в) = -1,4а - 3,4в
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Пошаговое объяснение:
(3а + 6в)/2 = 5
3а + 6в = 5 * 2
3а + 6в = 10
3а = 10 - 6в | : 3
а = 10/3 - 6/3в
а = 3 1/3 - 2в
-(4а + 2,1в) + (0,4в - 3,3а) - (1,7в - 5,9а) =
-4а - 2,1в + 0,4в - 3,3а - 1,7в + 5,9а =
(-4а - 3,3а + 5,9а) + (-2,1в + 0,4в - 1,7в) =
-1,4а + (-3,4в) = -1,4а - 3,4в